OCULAR DELIVERY OF NATAMYCIN SOLID LIPID NANOPARTICLE LOADED MUCOADHESIVE GEL: FORMULATION, CHARACTERIZATION AND IN VIVO STUDY - ABDELMONEM, REHAB; EL-NABARAWI, MOHAMED A.; ATTIA, ALSHIMAA M.; TEAIMAA, MAHMOUD (International Journal of Applied Pharmaceutics, 2020)
Objective: This study aimed to develop a novel topical ocular system of natamycin (NAT) by formulating and evaluating of NAT-solid lipid nanoparticle (SLN) loaded on mucoadhesive gels to improve its therapeutic activity and reduce the frequency of dosage to assist patient compliance. Methods: SLNs were prepared using lipids and Tween 80 or Pluronic F127 as stabilizers via modified high shear homogenization and ultrasound techniques. The prepared SLNs were characterized for particle size (PS), zeta potential (ZP), polydispersity index (PI), and entrapment efficiency percentage (EE %). The morphological examination for chosen SLNs was done using a transmission electron microscope (TEM). Carbapol 940 and Hydroxypropyl methylcellulose (HPMC) was incorporated with selected NAT-SLNs to form mucoadhesive gels. The prepared NAT-SLN gels were evaluated for drug content, mucoadhesion force, release study, and in vitro microbiological activity. In vivo study for the chosen formulae was done to evaluate its efficacy against keratitis in rabbits. Results: NAT-SLNs exhibited high EE % up to 99.167% and PS ranging from 128.35 to 1719.5 nm, with negatively charged ZP that confirmed the stability of SLNs. The NAT-SLN gels provided the high mucoadhesive force with a controlled release manner compared with the marketed-product MP. The in vivo experimental studies and histopathological examination showed the superiority of G2 (NAT-SLN (5% Pluronic F127 and 1:1 mixed lipid) 4% HPMC) over MP against Candida keratitis. Conclusion: According to the obtained results, G2 provided an effective pharmaceutical system against fungal keratitis in a controlled release manner compared with MP for reducing dosage frequency.